Pengaruh Pendidikan Terhadap Kepuasan Kerja Melalui Kinerja Guru SMPI Miftahul Ulum Tambelangan Kabupaten Sampang - Fatthurosi Fatthurosi; Chamariyah Chamariyah; Ninik Suryani (Journal of Management and Creative Business, 2024)
This type of research is explanatory, namely to test the hypothesis between hypothesized variables that will be tested. using a quantitative approach, the research sample was 42 respondents. In this study the data will be processed using SEM-PLS data analysis.The objectives of this study are: 1) To test and analyze whether education has a significant effect on job satisfaction. 2) To test and analyze whether education has a significant effect on teacher performance. 3) To test and analyze whether teacher performance has a significant effect on job satisfaction. 4) To test and analyze whether education has a significant indirect effect on job satisfaction mediated by teacher performance.The results showed that: 1) Education has a positive and significant effect on job satisfaction. This is evidenced by the original sample value of 0.174 and p-values of 0.045. 2) Education has a positive and significant effect on performance. This is evidenced by the original sample value of 0.335, and the p-values of 0.021. 3) Teacher performance has a positive and significant effect on job satisfaction. This is evidenced by the original sample value of 0.717 and p-values of 0.000. 4) Education has a significant positive effect on job satisfaction mediated by teacher performance. This is evidenced by the original sample value of 0.240 and the p-values of 0.002.